Translation and cross-cultural adaptation of the young children participation and environment measure for its use in Austria, Germany, and Switzerland - Krieger, Beate; Ederer, Friedrich; Amann, Ruth; Morgenthaler, Thomas; Schulze, Christina; Dawal, Britta (Frontiers in Pediatrics, 2024)
Background Concepts such as participation and environment may differ across cultures. Consequently, cultural equivalence must be assured when using a measure like the Young Children Participation and Environment Measure (YC-PEM) in other settings than the original English-speaking contexts. This study aimed to cross-culturally translate and adapt the YC-PEM into German as it is used in Germany, Austria, and Switzerland. Methods Following international guidelines, two translations were compared, and the research and expert team made the first adaptations. Twelve caregivers of children with and without disabilities from three German-speaking countries participated in two rounds of think-aloud interviews. Data were analyzed by content analysis to look for item, semantic, operational, conceptual, and measurement equivalence to reach a cultural equivalence version in German. Results Adaptations were needed in all fields but prominently in item, operational, and conceptual equivalence. Operational equivalence resulted in graphical adaptations in the instructions and questions to make the German version of YC-PEM, YC-PEM (G), more user-friendly. Conclusion This study presents a cross-cultural translation and adaptation process to develop a German version of the YC-PEM suitable for Germany, Austria, and Switzerland. A culturally adapted YC-PEM (G) is now available for research, practice, and further validation.